Perancangan Sistem Pengisian dan Pembacaan Data Informasi Benda Kerja pada Flexible Manufacturing System dengan Memanfaatkan Teknologi Radio Frequency Identification - Utomo, Anggoro Prasetyo; Setiawan, Ari; Gunarto, Frendy Z. (Yayasan Petra Harapan Bangsa, 2018)
Flexible Manufacturing System (FMS) is a manufacturing system consists of Computerized Numerical Control (CNC) machines which are integrated with computer-controlled material handling systems. CNC machine is equipped with a pallet buffer for storing work piece waiting to be processed, while another is being processed inside the machining room. The equipment to replace the work piece from the buffer to the machining room, is Automatic Pallet Changer (APC). CNC machine is also equipped with Automatic Tool Changer (ATC). ATC helps changing the cutting tools automatically in each operation. Work pieces have two surfaces to process, each surface is processed in several operations in one stage. For processing the workpiece, the automatic storage and retrieval system (AS/RS) requires information such as part number, number of stages, number and sequence of operation, operation time and type of cutting tool needed. The purpose of this study is to design system for reading and writing product data information in the FMS, using Radio Frequency Identification (RFID) technology. RFID Reader will be placed on loading/unloading station, stacker crane, pallet stocker, CNC machine and buffer per machine, while RFID tag will be placed on pallets. Thus RFID reader will read RFID tag containing unique identity (UID) which will be connected with part number, number of stages, number and sequence of machining operation, operation time, type of cutting tool and location in real time. This data will be used by stacker crane to deliver the work piece according to its purpose.Flexible Manufacturing System (FMS) adalah sistem manufaktur yang tersusun dari mesin-mesin Computerized Numerical Control (CNC) yang terintegrasi dengan sistem penanganan material yang dikendalikan oleh komputer. Mesin CNC dilengkapi sebuah buffer untuk menyimpan benda kerja yang menunggu untuk diproses, sementara sebuah pekerjaan sedang diproses di dalam mesin. Proses penggantian benda kerja dari buffer ke ruang mesin dilakukan menggunakan Automatic Pallet Changer (APC). Mesin CNC juga dilengkapi dengan Automatic Tool Changer (ATC), yaitu alat yang dapat mengganti perkakas potong secara otomatis. Data status pekerjaan merupakan hal terpenting agar FMS dapat beroperasi tanpa awak. Sistem penanganan material berupa automatic storage and retrieval system (AS/RS) akan bekerja secara otomatis berdasarkan informasi berupa: part number, jumlah stage, jumlah dan urutan operasi, waktu operasi dan jenis perkakas potong mana saja yang diperlukan. Informasi ini tersimpan sebagai data produk dan melekat pada benda kerja. Pada penelitian ini akan dirancang sistem pengisian dan pembacaan data informasi benda kerja menggunakan teknologi Radio Frequency Identification (RFID). Rancangan dikembangkan menggunakan RFID reader yang diletakkan pada loading/unloading station, stacker crane, pallet stocker, mesin CNC dan buffer tiap mesin. RFID tag akan diletakkan pada setiap pallet. Dengan demikian RFID reader akan membaca RFID tag yang berisi unique identity (UID) yang akan dihubungkan dengan part number, lengkap dengan informasi jumlah stage, jumlah dan urutan operasi pemesinan, waktu operasi, jenis perkakas potong, serta lokasi secara real-time. Data ini selanjutnya akan digunakan oleh stacker crane untuk mengantar benda kerja sesuai dengan tujuannya.